Evaluation of Anticonvulsant Potential of Methanolic Extract of Stem Bark Of Bombax Ceiba In Albino Mice - Fathima, Syeda Nishat; M, Rama; P, Shree Usha (Asian Journal of Pharmaceutical Research and Development, 2015)
To evaluate anticonvulsant potential of Methanolic extract of stem bark of Bombax ceiba in albino mice. The Methanolic extract of stem bark of Bombax ceiba was studied for its anticonvulsant effect on maximal electroshock induced seizures and Pentylenete trazole induced seizures and Strychnine induced seizures in mice. The duration of hind limb tonic extension in case maximal electroshock induced seizures and onset of convulsions and percentage protection offered by the extract in case of Pentylene tetrazole induced seizures and Strychnine induced seizures were noted. The Methanolic extract of stem bark of Bombax ceiba significantly reduced the duration of seizures by maximal electroshock induced seizures and delayed the onset of tonic seizures produced by Pentylene tetrazole and Strychnine. The data suggest that the Methanolic extract of stem bark of Bombax ceiba will produce its anticonvulsive effect via non-specific mechanisms may be by acting on voltage dependent sodium ion channels since it reduced the duration of seizures produced by maximal electroshock, GABAergic system as well as glycinergic system as it delayed the latency of seizures produced by Pentylene tetrazole and Strychnine.